Genetic improvement through genomic prediction for Pythium spp in lines common bean - Diaz, Lucy Milena; Arredondo, Victoria; Ariza-Suárez, Daniel; Aparicio, Johan Steven; Buendia, Hector Fabio; Cajiao V., César Hernando; Mosquera, Gloria; Beebe, Stephen E.; Mukankusi, Clare Mugisha; Raatz, Bodo (International Center for Tropical Agriculture, 2020)
Phenotypic and genotypic data for bean root disease and Pythium in common bean